Pathological Mechanism and Clinical Therapy Progress of Schlemm’s Canal - Yasha Zhou; Zhenxin Liu; Wenyong Gao; Yijing Yang; Qinghua Peng; Hanyu Tan (Journal of Ophthalmology)
Schlemm’s canal (SC) is a small circular canal in the deep part of the sclera at the junction of the sclera and cornea. As an integral component of the aqueous humor outflow, its structure and function are essential in regulating intraocular pressure (IOP). If SC develops lesions, the drainage of aqueous humor would be obstructed, leading to increased intraocular pressure and injury to the optic nerve. With the rapid development of minimally invasive glaucoma surgery, an increasing number of surgeons became familiar with SC, and the area generated substantial academic attention. The pathological mechanism and the therapy for SC that had been studied in recent years are summarized in this article, hoping to provide ideas for the treatment of glaucoma in the future.